Teacher Professional Activity in Educational Process of Higher Educational Institution - Коць, Михайло Онисимович; Kots, Mykhailo O. (Ариэльский университетский центр в Самарии (г. Ариэль, Израиль), 2015)
The theoretical analysis and empirical research relating to peculiarities of teacher professional activity in educational process of higher educational institution depending on work experience and age are conducted in the article. It is substantiated that in modern psychology issues of personality's subject activity, its creative role in life transformation remain relevant. The article specifies that the activity of pedagogical interaction subjects is linked to teaching process and interaction. Entire subject activity in pedagogical interaction integrates various manifestations of activity, the most important for this action, which is the potential of their activity. The aim of the study was to investigate the characteristics of professional activity of higher educational institution teachers depending on work experience and age. The study involved the teachers of Ukrainian universities: Rivne State Humanities University, Vasyl Stefanyk Carpathian National University, Lesia Ukrainka Eastern European National University. Total sample – 124 persons. According to the "professional activity of teachers" method (TAQ) we have established the relationship between educational activity components, such as teacher professional activity motivation, self-evaluation of abilities to self-realization in this life sphere, emotion control in professional sphere, professional activity dynamics, rigid reproduction-modification activity, effective component of teacher pedagogical activity in educational process of higher education institution. The differences in professional activity manifestation of university teachers with different experience are revealed. Different type of professional orientation is discovered. University teachers with seniority from 1 to 5 years demonstrate effective component of teacher professional activity, teachers with experience of 5 to 10 years – self abilities at self-realization in this life sphere, teachers with experience of over 10 years – teacher professional activity motivation.
Keywords: teacher; institution of higher education; professional activity; educational process